2015
DOI: 10.1177/1049732315570122
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences of Health Care for Their Children With Cerebral Palsy

Abstract: Although current health care service delivery approaches for children with cerebral palsy recognize the importance of including parents in the health care of their child, we do not yet understand how parents experience this phenomenon. In this study, we used grounded theory methodology to explore parents' experiences of health care for their children with cerebral palsy living in a regional area of Australia. Our findings indicate that parents experience health care for their child as a cyclical process of "ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 53 publications
5
41
0
4
Order By: Relevance
“…Parents of disabled children identify the provision of information about their child's condition and the provision of services as one of their core needs (Sahay, Prakash, Khaique, & Kumar, ). Some parents in this research found out important information by “accident,” a finding reported in other studies (Redmond & Richardson, ; Maddison & Beresford, ; Hayles et al, ). It is encouraging, however, that parents of autistic children in this research reported a marked increase in the availability of information about autism and available services over time.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Parents of disabled children identify the provision of information about their child's condition and the provision of services as one of their core needs (Sahay, Prakash, Khaique, & Kumar, ). Some parents in this research found out important information by “accident,” a finding reported in other studies (Redmond & Richardson, ; Maddison & Beresford, ; Hayles et al, ). It is encouraging, however, that parents of autistic children in this research reported a marked increase in the availability of information about autism and available services over time.…”
Section: Discussionsupporting
confidence: 77%
“…Parents of disabled children continue to highlight the importance of feeling empowered and working in partnership with professionals (Hayles et al, 2015), and such an approach was evidenced in this research. The lead role of mothers in caring for and making decisions with professionals about their disabled child was evident from participants' accounts and mirrors the findings of previous studies, such as those summarized by Read (2000).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…L'information constitue un besoin fondamental (King et al, 2017). Or, malgré la volonté des organisations de bien informer leurs utilisateurs, il semble que l'information sur les services est souvent obtenue de façon informelle ou par l'entremise des autres familles ou des amis, plutôt que par les professionnels de l'organisation (Girard, Miron & Couture, 2014;O'Reilly, Karim & Lester, 2014;Redmond & Richardson, 2003;Samuel et al, 2012), et parfois, les informations sont acquises par hasard, sans démarche systématique de la part des organisations qui les desservent (Hayles, Harvey, Plummer & Jones, 2015).…”
Section: Le Besoin D'être Informé Sur Les Servicesunclassified
“…Les familles ayant accès à de l'information pertinente seraient aussi plus aptes à gérer le stress et à offrir des soins à leur enfant. Finalement, l'accès à une information pertinente et facile à saisir facilite la compréhension d'un diagnostic ou d'une condition particulière, ce qui améliore la prise de décision quant à leur santé, ultimement à l'accès aux services et, en concomitance, augmente le bien-être de la famille (Hayles et al, 2015).…”
Section: L'accès à L'information Et Le Pouvoir D'agirunclassified